Manifestations of Post-Truth after Cancellation of Indonesia as the U20 World Cup Host - Agustina, Widi Asmarani; Prihantoro, Edy; Mujiyana; Utami, Sabrina Rahma (Asian Journal of Media and Communication, 2023)
The research aims to see the realm of post-truth after the cancellation of Indonesia as the host of the U20 World Cup. Applying the participatory culture theory, this study used a qualitative approach. It founds that the phenomena of post-truth can be seen from the statement of Ganjar Pranowo, the Governor of Central Java Province, in refusing the participation of the Israeli National Team to play in Indonesia, which reaps the pros and cons on social media, and further grow fake news. After fact-checking has been carried out on some pros and cons, some news may be classified as fake news by irresponsible persons. It can be concluded that Indonesian society has already entered the post-truth era, characterized by many people believing in the issues merely based on their own interests and alignments. At this point, fact-checking efforts should be used as a basis for receiving any information.